The Luck of the Loch Ness Monster : A Tale of Picky Eating - Flaherty, Alice; Magoon, Scott (Boston : Houghton Mifflin, 2007)
A young American girl's picky eating habits transform a small worm into the famous Loch Ness Monster, with facts about the biology of pickiness.
Keywords: Eating customs -- Fiction; Diet -- Fiction; Loch Ness monster -- Fiction; Scotland -- Fiction